House Selection Decision Support System with Fuzzy Tsukamoto Method - Tomi Irnawandi Tafonae (International Journal of Basic and Applied Science, 2019)
Housing is a basic human need and needs to be fostered and developed for the sake of continuity and improvement of people's lives and settlements which cannot be seen as they mean of need, but more than that it is a human settlement in creating a space of life to promote themselves in revealing their identity. During this time the decision making of home selection desired by consumers still experienced several obstacles, namely the slow process of decision making, inconvenience to the housing environment, credit installments and so on. This is because there is no objective method for deciding on a fast choice based on housing data which is right in accordance with consumer desires. By referring to the solution given by Fuzzy Tsukamoto in helping to make a decision, a decision maker can make decisions about housing according to the desired quickly by comparing all existing criteria. Decision support systems are generally defined as a system that is capable of producing solutions and handling problems. Decision support systems are not intended to replace the role of decision makers, but to help and support decision makers. This Fuzzy Tsukamoto method can determine the preference value of each alternative, and can select the best alternative from a number of alternatives.